Removal of Cr(VI) by Immobilized Consortium of Freshwater Microalgae in Batch and Continuous System - Samuel, Jastin; Lien Paul, Madona; Kumari, Jyoti; Ravikumar, K.V.G.; Natarajan, Chandrasekaran; Mukherjee, Amitava (Asian Journal of Chemistry, 2015)
The potential of an adsorption coupled reduction process for removal of chromium(VI) was evaluated using immobilized algal consortium (of fresh water isolates, Oocystis, Nostoc, Syncoccus and Desimococcus species) through batch reactor studies. The batch sorption capacity of algae was substantially enhanced on adaptation to Cr(VI) and consortium formation (83.53 mg/g). The batch data followed Langmuir isotherm and pseudo first order kinetics. The effective applicability of the sorbent for Cr(VI) removal was tested in packed bed column reactor. At the adsorbent dosage of 1 g/L, flow rate of 3 mL/min, bed height of 20 cm and initial Cr(VI) concentration of 300 mg/L, maximum adsorption capacity of 579.2 mg/g was achieved. The possible mechanism of adsorption and reduction of Cr(VI) was explained by Fourier transform infrared spectroscopy and electron paramagnetic resonance spectroscopy analysis confirmed the reduction of Cr(VI) to Cr(III) on the sorbent surface.